A Study On Urine Analysis Parameters and Antimicrobial Susceptibility of Uropathogens Among Children of Suspected Uti in A Tertiary Care Hospital - Nampelli, Ganesh; Reddy Gunnala, Santosh; Nimmagadda, Rachana; Kumar Redy, Vangala Sateesh (Journal of Neonatal Surgery, 2025)
Background: Urinary tract infections (UTIs) are the most frequently seen genitourinary condition in children. A urinary tract infection refers to any infection affecting the kidneys, ureters, bladder, or urethra (1). This represents a serious concern that pediatric healthcare providers regularly encounter and is one of the most common bacterial infections encountered in typical clinical settings (2, 3). Objectives: To determine the prevalence of UTI among the children of suspected UTI, urinary tract anomalies, and fever without focus. Material & Methods: Study Design: Hospital-based Cross-sectional study. Study area: The study was conducted in the Department of Paediatrics. Study Period: 1 year. Study population: All children who were admitted in the paediatric department during the study period and fulfilled study criteria were enrolled. Sample size: The study consisted of a total of 210subjects. Results: Among the urine culture positive cases, urinary tract defects are seen in 52.4 % of the population that is 18 out of 34 culture positive cases. The most common urinary tract defect seen in UTI positive patients is hydronephrosis. 7 out of 34 (20.5%) population were having hydronephrosis and 4(11.7%) have hypospadias and the rest were having renal caliculi (8.4%) and PUJ obstruction (4.48%). The prevalence of urinary tract anomalies in children with urinary tract infection was found out to be 52.4%. Conclusion: While urine culture is considered the definitive method for diagnosing a urinary tract infection (UTI), it can be time-consuming and expensive. Therefore, evaluating additional parameters can aid in the early identification and prompt initiation of antibiotic treatment. This research offers important insights into urine analysis markers such as pus cells, leukocyte esterase, and nitrite